Adsorption of methylene blue using green pea peels (Pisum sativum): a cost-effective option for dye-based wastewater treatment - Dod, Ramesh; Banerjee, Goutam; Saini, S. (Biotechnology and Bioprocess Engineering, 2012)
Methylene blue (MB), a common toxic dye, is largely discharged from dyeing processes for acrylic, nylon, silk, and woolen fabrics in textile industries. While application of conventional removal processes like chemical precipitation, ion exchange, commercial activated carbon adsorption, etc often become cost-prohibitive, the adsorption of MB by abundantly available green pea peel (GPP: Pisum sativum) derived and acid-treated carbon (GPP-AC) has proved to be a cost-attractive option in the present study. The physicochemical and morphological characteristics of GPP-AC were examined with the help of XRD, BET surface area, SEM, and Fourier transform infrared spectrophotometry ((FT-IR) analysis. The influences of such adsorption parameters as initial dye concentration, pH, contact time, adsorbent dosage, agitation speed, particle size, and temperature were evaluated and optimized. The equilibrium contact time for maximum adsorption of MB on to GPPAC was found to be 7 h. The equilibrium data of the adsorption process were modeled by using the Langmuir, Freundlich, Temkin, and Dubinin-Raduskevich (D-R) isotherms. However, the adsorption equilibrium data were best described by the Langmuir Isotherm model, with a maximum adsorption capacity of 163.94 mg MB/g GPPAC at 30A degrees C.
Keywords: Adsorption; Dubinin-raduskevich; Freundlich; green peas peels; Isotherms; Langmuir; Methylene blue; Temkin